A study of characteristics and applications of ionic liquids - Etlana Yusari Dhaniardi (2012)
This study explores a method to measure Hildebrand solubility parameter (δH) of ionic liquids which is one of the characteristics of ionic liquids. δH can be used to determine properties of ionic liquids as δH is a good indicator of solubility due to estimation of the degree of interaction between materials it provides. Materials with comparable values of δH are expected to be miscible of each other. The results from this present study show that δH of ionic liquids can be determined by measuring their intrinsic viscosities in a series of solvents with known solubility parameters. δH of ionic liquids is obtained as the value of δH when the intrinsic viscosity reaches maximum point. This present study determines δH of 1-butyl-3-methylimidazolium hexafluorophosphate by intrinsic viscosity method.